Odontogén tályogok diagnosztikája és kezelése a nemzetközi ajánlások tükrében [Current approaches to the diagnosis and management of odontogenic abscesses] - Vetró Éva (ORVOSI HETILAP, 2022)
A wide scale of medical professionals including general practitioners, dentists, maxillofacial surgeons, otolaryngologists or even emergency physicians frequently encounter patients suffering from abscesses of odontogenic origin. These dental infections spreading along the fascial planes into the adjacent anatomical spaces or by the lymphatic vessels and veins may result in life-threatening situations. It is essential to prevent and - in the case of an evolved disease pattern - to treat them properly, since improper or delayed treatment may entail avoidable burdens on the healthcare system. Our aim was to review the current literature regarding the development, diagnostics and treatment of odontogenic infections. A review of the English and Hungarian literature was performed. Considerations regarding the surgical management of dental abscesses have well-tried, traditional routes. Prompt intervention is considered mandatory with surgical decompression of the swelling by performing incision and drainage. A rapid improvement of radiology has provided the possibility to realize and avoid fatal consequences of this disorder. The administration route, necessity and duration of empiric antibiotic therapy are still "debated", protocols vary across studies. Based on inconsistency in findings among the studies and lack of high-quality prospective studies, future research should evaluate evidence-based and effective management of dental abscesses. Orv Hetil. 2022; 163(37): 1455-1463.